Using Financial Accounting Data to Examine the Effect of Foreign Operations Located in Tax Havens and Other Countries on U.S. Multinational Firms' Tax Rates - DYRENG, SCOTT D.; LINDSEY, BRADLEY P. (Journal of Accounting Research, 2009)
ABSTRACT This paper investigates the effect tax havens and other foreign jurisdictions have on the income tax rates of multinational firms based in the United States. We develop a new regression methodology using financial accounting data to estimate the average worldwide, federal, and foreign tax rates on worldwide, federal, and foreign pretax book income for a large sample of U.S. firms with and without tax haven operations. We find that on average U.S. firms that disclosed material operations in at least one tax haven country have a worldwide tax burden on worldwide income that is approximately 1.5 percentage points lower than firms without operations in at least one tax haven country. Our results also show that U.S. firms face a 4.4% current federal tax rate on foreign income whether or not they have tax haven operations. Finally, we find that U.S. firms with operations in some tax haven countries have higher federal tax rates on foreign income than other firms. This result suggests that in some cases, tax haven operations may increase U.S. tax collections at the expense of foreign country tax collections.